الآثار الاقتصادية والاجتماعية للديون الخارجية على البلدان العربية غير النفطية - زنبوعة, محمود; أبا زيد, ثناء; بلال, حافظ (Latakia University Journal - Economic and Legal Sciences Series, 2019)
أصبحت مشكلة الديون الخارجية اـتي نمت إلى مستويات عالية في العقود الأخيرة من أخطر وأعقد القضايا التي تواجه الاقتصاد العربي وتمنعه من الانطلاق نحو تحقيق خطوات تنموية شاملة، تمكنه من مواجهة التحديات الخارجية. فقد نمت تلك الديون بسبب مجموعة من العوامل الخارجية و السياسات الاقتصادية والتنموية الخاطئة والتي نظرت إلى الموارد الخارجية على أنها بديل للموارد المحلية، كما أنها عجزت عن إيجاد الحلول الكفيلة بإيجاد مخرج تنموي يساعد على سداد تلك الديون لذلك فإن نجاح الدول العربية في بناء مشروع تنموي مستقل يتطلب أن تكون أهمية التمويل الخارجي متناقصة عبر الزمن وأن تكون أهمية التمويل المحلي متنامية باستمرار وذلك بالعمل على رفع معدل الادخار المحلي . Arab external debts have risen to high levels in recent decades, creating one of the most dangerous and complicated problems for the Arab economy. External debts stand in the way of Arab economy, hindering its moves towards comprehensive development that enables it to face external challenges. External debts have grown because of a number of external factors and wrong internal economic policies, which saw external resources as alternative to local ones, and which failed to come up with creative solutions that enable the countries to pay off their debts. Therefore, for a Arab countries to succeed in drawing a developmental project requires less reliance on external financing and a growing reliance on local money through increase of the rate of local savings.